2020
DOI: 10.1177/1474515120903614
|View full text |Cite
|
Sign up to set email alerts
|

Employment status three years after percutaneous coronary intervention and predictors for being employed: A nationwide prospective cohort study

Abstract: Background: Vocational support is recommended for patients in cardiac rehabilitation (CR), as returning to work is important in patients social readjusting after an acute coronary event. Information is lacking on whether CR leads to higher long-term employment after percutaneous coronary intervention (PCI). Aims: The aims of this study were to determine employment status three years after PCI, to compare employment status between CR participants and CR non-participants and to assess predictors for employment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…No difference was found between the study groups in the participation rates in cardiac rehab programs. No or little effect of cardiac rehab enrollment on employment status was observed in many other studies; 6,28 and was also the overall finding of Hegewald et al 27 who conducted a systematic review of 39 randomized controlled trials that aimed to evaluate the effects of interventions intended to enhance return-to-work in patients with coronary heart disease compared to usual vs. no care. To illustrate, they found that person-directed combined interventions, applying both psychological counseling and physical conditioning versus usual care, may have increased return-to-work for up to six months.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…No difference was found between the study groups in the participation rates in cardiac rehab programs. No or little effect of cardiac rehab enrollment on employment status was observed in many other studies; 6,28 and was also the overall finding of Hegewald et al 27 who conducted a systematic review of 39 randomized controlled trials that aimed to evaluate the effects of interventions intended to enhance return-to-work in patients with coronary heart disease compared to usual vs. no care. To illustrate, they found that person-directed combined interventions, applying both psychological counseling and physical conditioning versus usual care, may have increased return-to-work for up to six months.…”
Section: Discussionmentioning
confidence: 74%
“…Not unexpected, the employment rate of patients in the control group, is very similar to that observed in other studies in which typically short-term cardiac rehabilitation was employed. 4,6,26 The success of the comprehensive case-management program in facilitating long-term maintenance of employment may be explained, in addition to the factors mentioned above, by containing other components of disability management/vocational rehabilitation programs, suggested by rehabilitation specialists as important for enhancing work re-integration, namely: occupational counseling, monitoring and providing support and alleviating any difficulties during work reintegration, addressing personal and work related-obstacles that might affect an individual's decision to return-to-work, and providing coordination between all relevant parties. 6,7,27,28 The majority of the participants in this study participated in a regular cardiac rehab program (see Methods).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of 3291 patients with CHD in 24 European countries found that 76% of patients could return to work within 6 months to 3 years after discharge [ 9 ]. A prospective cohort study carried out by Norwegian scholars found that approximately 89% of patients returned to work 3 years after PCI [ 11 ]. The results of a questionnaire survey conducted by Wang on 428 patients 3 years after PCI revealed that 5.7% of patients were unable to work or had serious health problems at work, and 58.8% of patients had a significant decrease in work level and needed to reduce their work hours [ 12 ].…”
Section: Introductionmentioning
confidence: 99%